2020
DOI: 10.1111/tpj.14960
|View full text |Cite
|
Sign up to set email alerts
|

Soybean BARCSoySNP6K: An assay for soybean genetics and breeding research

Abstract: The limited number of recombinant events in recombinant inbred lines suggests that for a biparental population with a limited number of recombinant inbred lines, it is unnecessary to genotype the lines with many markers. For genomic prediction and selection, previous studies have demonstrated that only 1000-2000 genome-wide common markers across all lines/accessions are needed to reach maximum efficiency of genomic prediction in populations. Evaluation of too many markers will not only increase the cost but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 87 publications
0
64
0
Order By: Relevance
“…A 10 kb-genomic region spanning a significant SNP was used for candidate gene search using the G. max Williams 82.a2 reference in Soybase (https://www.soybase.org/) [34]. The SNPs associated with the combined data over three years for maturity date, plant height, seed weight, and yield were used for candidate gene discovery.…”
Section: Candidate Gene Discoverymentioning
confidence: 99%
“…A 10 kb-genomic region spanning a significant SNP was used for candidate gene search using the G. max Williams 82.a2 reference in Soybase (https://www.soybase.org/) [34]. The SNPs associated with the combined data over three years for maturity date, plant height, seed weight, and yield were used for candidate gene discovery.…”
Section: Candidate Gene Discoverymentioning
confidence: 99%
“…DNA concentration was quantified with a spectrophotometer (NanoDrop Technologies Inc., Centreville, DE, USA) and then normalized at 50 ng/μL for genotyping. SNP genotyping was performed in the Soybean Genomics and Improvement Laboratory, USDA-ARS, Beltsville, MD, USA, using the Illumina Infinium SoySNP6K BeadChips (Illumina, Inc. San Diego, CA, USA) as previously described [53]. Subsequently, SNP alleles were called using GenomeStudio Genotyping Module 2.0 (Illumina, Inc. San Diego, CA).…”
Section: Dna Isolation Snp Genotyping and Genetic Map Constructionmentioning
confidence: 99%
“…Here, we found that sampling SNPs located within genic regions was more informative than sampling SNPs from intergenic or random regions, and therefore marker effects do not need to be considered for each different population. Indeed, sampling SNPs from genic regions can ensure or even signi cantly improve the accuracy of prediction and reduce sequencing costs (Song et al 2020). In addition, expanding the training group can also improve the accuracy of predictions (Hao et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite low SNP density, previously developed soybean arrays have been used in diversity analysis, genetic mapping, and association analysis, etc. (Shen et al 2005;Song 2014; Song et al 2020;Wang et al 2018b). More recently, high density soybean arrays have been successively developed.…”
Section: Introductionmentioning
confidence: 99%